MASA PEMBAHARUAN PENDIDIKAN ISLAM - Nadya Fadhilah; Nur Asikin; Anggun; Lutfi Nurmaidah; Widya Nur Asyifa; Sriliza (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study aims to examine the period of Islamic education reform and analyze its background, challenges, and impacts on the Islamic education system. The main issues addressed in this research are the lag of Islamic education in responding to scientific and technological developments and the demands of the modern era, as well as the dualism between traditional and modern educational systems. This research employs a qualitative method with a library research approach by reviewing various written sources, including books, academic journals, and relevant documents related to Islamic education reform. The data are analyzed using a descriptive-analytical technique to obtain a comprehensive and systematic understanding. The results show that Islamic education reform is characterized by efforts to integrate religious and general knowledge, curriculum renewal, innovation in teaching methods, and the strengthening of Islamic educational institutions to face global challenges without neglecting Islamic values. Therefore, Islamic education reform plays a strategic role in producing knowledgeable, ethical, and adaptive Muslim generations in a changing world